DXA-derived visceral adipose tissue reference values and metabolic syndrome risk threshold in an Algerian adult population - Mohammed Hadi Bestaoui; Ali Lounici; Amar Tebaibia; Latifa Henaoui; Nawal Brikci-Nigassa; Houssem Baghous; Amel Bensefia (PLoS ONE, 2025)
Background Visceral adipose tissue (VAT) is associated with several cardiometabolic risk factors, particularly metabolic syndrome and insulin resistance. Reference values for VAT vary across populations, genders, and ages. Data on visceral fat in the Algerian population are lacking. This study aimed to establish reference values for VAT in a general adult population. The secondary objectives were to determine cardiometabolic consequences and to propose suggested threshold values for VAT to predict metabolic syndrome. Materials and methods This cross-sectional, analytical study randomly selected participants from the electoral list of Tlemcen, Algeria. VAT was measured using dual-energy X-ray absorptiometry (DXA) General Electric Healthcare© Lunar iDXA. Results A total of 301 adults (147 men and 154 women) with a mean age of 49.3 ± 15.1 years participated. The median (25th-75th percentiles) VAT mass was 1364 g (690–2049) in men and 1060 g (585–1590) in women. Binary logistic regression analyses demonstrated that cardiometabolic risk factors, including hypertension, type 2 diabetes, dyslipidemia, metabolic syndrome, insulin resistance according to HOMA2-IR, hepatic steatosis, and sleep apnea syndrome, were significantly dependent on VAT mass. Threshold values for VAT to predict metabolic syndrome (according to International Diabetes Federation) were ≥ 1369 g in men (sensitivity: 86.2%, specificity: 74.2%, Youden’s index: 0.604) and ≥ 1082 g in women (sensitivity: 76.3%, specificity: 76.9%, Youden’s index: 0.532). Conclusion This study provides reference values for VAT in an urban Algerian adult population and highlights its importance in assessing cardiometabolic risk.